The active surface area increase of rhodium electrodes through electroreduction of oxide layers produced by fast periodic potentials - Chialvo, Abel César (1987)
Fast periodic potentials applied to polycrystalline rhodium electrodes in acid and base electrolytes can cause, under certain conditions, the growth of hydrous oxide layers which after their electroreduction yield reproducible electrode surfaces with a large increase in the active surface area. These processes were investigated at 30° C by changing systematically the parameters of the perturbing potential including potentiostatic steps. The most suitable conditions for growing oxide layers capable of producing an increase in the rhodium electrode active surface area after their electroreduction correspond to a square wave perturbing potential at 1.8 kHz and a potential window between −0.025 and 2.0 V (vs. RHE). The processes related to the formation of anodic oxide layers under different experimental conditions are discussed.